SOCIAL PSYCHOLOGICAL CHARACTERISTICS OF THE DYSFUNCTIONAL FAMILY (Academicia Globe: Inderscience Research, 2022)
In this article, information is given about the place and role of the development of the spirituality of the individual in the so-called family. In addition, there are types of families about defective families and why there are more and more decisions in families, who are the reasons for this. Information is given about how many children become orphans after this family. It has been repeatedly emphasized that the role of father and mother in the family is very important and that the father is the head of the family.